Analisis Pengaruh Faktor Fundamental Terhadap Harga Saham Perusahaan Consumer Goods Yang Terdaftar Di Bursa Efek Indonesia (Bei) - Indra Widjaja, Ria Anggraeni dan (Universitas Tarumanagara, 2017)
The purpose of this research is to determine whether there is an influence between Debt Ratio (DR), Return on Asset (ROA), Return on Equity (ROE), Net Profit Margin (NPM) and Firm Size to consumer goods company’s stock price. This research examines eighteen consumer goods companies, which listed in Indonesia Stock Exchange (IDX) during 2012 to 2015. Sampling method that’s been used for this research is purposive sampling because the sample used in this research has been adapted to certain criteria. The hypothesis examined by using Scientific Program for Social Science (SPSS). Multiple regression analysis is being used to test some hypothesis about the effects of debt ratio (DR), return on asset (ROA), return on equity (ROE), net profit margin (NPM), and firm size to consumer goods company’s stock price. The results of this research show that debt ratio (DR), return on asset (ROA), return on equity (ROE), net profit margin (NPM), and firm size have significant effect to stock price simultaneously. Debt ratio and ROE do not have a partially significant effect on stock prices. Net Profit Margin (NPM) has a partially significant negative effect on stock prices. ROA and firm size have a partially significant positive influence to stock prices.